O caminho para Persépolis: intermidialidade, quadrinhos e animação - Gomez, Karla Angelica Fernandes [UNIFESP] (2019)
This M.A. thesis aims at analyzing the intermidiatic adaptation of the comic Persepolis (SATRAPI, 2007) to cinema, originating the animated film (also named Persepolis) directed by the author herself with Vincent Paronnaud. The research consists in investigating some excerpts from the source work and their rendering in the animated film, focusing on the transposition of content from one media (comic) to another (cinema, being the animated film a genre of this media). The theoretical framework used has as its key contributions the works by Rajewsky (2012) and Elleström (2017) on intermediality; Gaudreault & Marion (2012) on the concepts fabula and syuzhet; Boutin (2012) on multimodality; Genette (1982) and Gervais (2009) on intertextuality; Field (2014), Stam (2006) and Hutcheon (2013) on adaptation. The criteria for the analysis of the media studied here, comics and cinema, derive form works by Barbieri (2017), Cagnin (2014) and Nogueira (2010). The research hypothesis is that the adaptation represents a new product, a hypertext (the animation) which results from a hypotext (the comic), according to Genette’s nomenclature (1982). The process of meaning construction in the animated film was based on the characteristics of this media, which differs from those of the media comics, even though both are characterized by a multimodal language.